Pengaruh Model Problem Based Learning Dengan Strategi Everyone Is A Teacher Here Terhadap Kemampuan Komunikasi Matematis Dan Self-Confidence Siswa SMP - Taufik Rahman; Fauzia Nisa (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2020)
Mathematical communication ability is an important ability in learning mathematics where students interact directly with mathematics through mathematical communication, but the fact are student’s mathematical communication skills are still low. One of the reasons is the problem of student self-confidence is still low as well, for that self- confidence is needed. One alternative learning that can improve the ability of mathematical communication skills and self-confidence is the Problem Based Learning (PBL) learning model with the strategy Everyone is a Teacher Here (ETH). The purpose of this study were: 1) to know whether the improvement of student’s mathematical communication skills who obtain PBL models with ETH strategies were better than students who obtain conventional learning; 2) to know self-confidence of students who obtain PBL with ETH strategies better than students who obtain conventional learning; 3) to know whether there is a positive correlation between mathematical communication skills and self-confidence of students who obtain PBL with ETH strategies. The method used is quasi experiment. The population in this study were all eighth grade students of Baleendah 1 Junior High School with a sample of two randomly selected classes. The instrument used in the study was a test type description of mathematical communication ability questions and attitude scale using a Likert Scale model. The attitude scale contains statements about self-confidence. Processing and data analysis using t-test and correlation test with the help of Microsoft Excel software and SPSS 20.00 for windows software. The results showed that: 1) Improvement of students' mathematical communication skills using PBL learning model with ETH strategies was higher than students who used conventional model; 2) Self-confidence of students who use PBL learning model with ETH strategies is better than self-confidence students who use conventional model; 3) There is a positive correlation between students' mathematical communication and self-confidence of students who obtain PBL learning with ETH strategies. Therefore the PBL model with ETH strategy can be used as an alternative for teachers in carrying out classroom learning